Push and pull factor: determining the visitors’ satisfactions at urban recreational area / Noralizawati Mohamed and Noriah Othman - Mohamed, Noralizawati; Othman, Noriah (Universiti Teknologi MARA Cawangan Selangor, 2016)
This study investigates the visitors’ satisfaction at the most popular urban recreational area, Kepong Metropolitan Park, Selangor. It presents the analysis and synthesis of information collected from an open-ended survey. Selected visitors were asked to state their opinions regarding overall scene and the answers were summarized and categorized in terms of several dimensions. As a result, the researcher found that the visitors expressed several comments and suggestions that could be used as push and pull factors in determining their satisfaction in the recreational area. These two dimensional phenomenons are very useful as reference to researchers or designers to identify and fulfill the visitors’ satisfaction for future preparation of recreational area.